Measuring threshold effects in non-dynamic panels: the impact of terms of trade on FDI inflows under different regimes of institutional quality - Barone, Sergio; Descalzi, Ricardo L.; Navarrete, José Luis (2024)
Fil: Barone, Sergio. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.